2016
DOI: 10.1364/ol.41.003193
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced rotational Raman scattering in gases using a 20  mW near-infrared fiber laser

Abstract: A novel cavity-enhanced laser diagnostic has been developed to perform point measurements of spontaneous rotational Raman scattering. A narrow linewidth fiber laser source (1064 nm) is frequency locked to a high-finesse cavity containing the sample gas. Intracavity powers of 22 W are generated from 3.7 mW of incident laser power, corresponding to a buildup factor of 5900. A triple monochromator and a photomultiplier tube in counting mode are used to disperse and measure the scattering spectra. The system is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Indeed, when the optical frequency of the incident laser is in resonance with a longitudinal cavity mode of the optical resonator, a standing optical wave is formed between the resonator mirrors. A high-nesse optical resonator can signi cantly build up the laser power, by several orders of magnitude [25], directly enhancing the photoacoustic signal which scales linearly with the laser power. The laser intensity is modulated at the same resonance frequency as the acoustic resonator.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, when the optical frequency of the incident laser is in resonance with a longitudinal cavity mode of the optical resonator, a standing optical wave is formed between the resonator mirrors. A high-nesse optical resonator can signi cantly build up the laser power, by several orders of magnitude [25], directly enhancing the photoacoustic signal which scales linearly with the laser power. The laser intensity is modulated at the same resonance frequency as the acoustic resonator.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, this intrinsic drawback can be overcome by reasonable experimental setups and design of structural parameters. One promising method is to combine HCFs with cavity enhanced Raman spectroscopy (CERS) to increase the laser intensity [87][88][89][90][91][92][93][94][95][96][97] (more details on CERS are presented in review [97]), as shown in Fig. 9a, in which the two FBGs act as highly reflective mirrors to form an F-P cavity.…”
Section: Raman Spectroscopy-based Fibre Gas Sensormentioning
confidence: 99%
“…E.g., the CO 2 concentration is oftentimes inferred from the reading of a metal-oxide based, total volatile organic compound (TVOC) sensor, even though the correlation between TVOC and CO 2 is weak [15]. While Raman-based approaches may detect many gases simultaneously [16,17,18,19,20,21,22], techniques based on absorption spectroscopy are the most promising candidates for reliable CO 2 detection. Using tunable diode laser spectroscopy a high degree of sensitivity and specific, quantitative detection can be achieved, albeit at high associated costs in terms of optical and computational infrastructure as well as maintenance [23,24].…”
Section: Introductionmentioning
confidence: 99%